Estudos experimentais sobre relações derivadas e transferência do significado - Almeida, João Henrique de (2013)
Questions on how abstract symbols acquire meaning remain intriguing puzzles for behavioral and cognitive sciences. Recently, tow main approaches have been emphasized in the context of Behavior Analysis investigating these issues, the Stimulus Equivalence Paradigm and Relational Frame Theory. In this series of studies the main objective was to add data to discussion on this topic. In Study 1 it were investigated validity and accuracy of a Semantic Differential instrument which has been used to measure the transfer meanings equivalent stimuli. Factor analysis of the collected data provided indications of the validity of the instrument and the alpha coefficients obtained indicate that the two factors extracted in this analysis have acceptable levels of accuracy, although one of the factors must be revised. Study 2 described an experiment was conducted to evaluate the modification of meaning through reorganization of stimulus equivalence classes. Results showed the importance of delayed matching to sample in the transfer of functions to reorganized classes of equivalent stimuli. In Study 3, it was investigated the same phenomenon, the transfer functions, but in classes established primarily by reject control. The difficulty in establishing this type response pattern did not allowed clear inferences about the transfer with this specific type of control. Study 4 evaluated the transformation function using the IRAP. In the results we observed this phenomenon in both explicit and implicit measures. This set of studies allowed investigating different measures of transfer and transformation of functions, defined here as the study of meaning, and to observe important variables in this process especially the importance of establishing reliably relations between stimuli.